Kontrastif Kolokasi dalam Penerjemahan Arab-Indonesia - Susilawati, Ani (Qismul Arab: Journal of Arabic Education, 2022)
The comparative study conducted in this research is to see the differences and similarities between Arabic and Indonesian collocations and to see how the collocation process is translated. The comparative study was conducted using a comparative descriptive methodological approach. This research is a type of library research, which describes research conducted solely based on facts or phenomena contained in the data. The data processing process is carried out using three steps of contrastive analysis, the first is a description, the second is an overview and the third is a comparison as well as describes the collocation process in translation. Through these several stages, lexical and grammatical collocation data can be obtained both in Arabic and Indonesian as follows: words that are side by side or side by side between prepositions and verbs where the prepositions used are the prepositions (fî), ??(ilâ)??? (alâ), (an), ?(li) and (bi), resulting in the form or category of verb + preposition. Meanwhile, lexical collocations in Arabic use noun + noun, adjective + noun, verb + noun, preposition + noun and Indonesian lexical and grammatical collocations take the form of subject + predicate, noun + adjective, noun + noun, noun + adjective, noun + noun, verb + noun, adjective + noun. Furthermore, in the translation process, the lexical and grammatical collocation forms from the two languages cannot be translated literally or word for word (as is) but must be translated according to the context of the sentence and the culture used in the language.